PTH-087 Perceptions Of Liver Disease Amongst The Nepali Community; Designing Effective Case-finding Strategies To Test Uk Migrant Groups For Hbv And Hcv. (9th June 2014) - Petrova, M; Hendy, J; Zamani, J; Dunstall, M; Mathew, S; Margot, N; Berry, P; Foster, G; Lisa, M; Kennedy, P; Ala, A
Abstract : Introduction: Identifying at-risk migrant groups for Hepatitis B and C (HBV and HCV) is well established. The UK Nepali community has grown rapidly since 2004, when settlement rights were given for ex-Gurkha servicemen and dependants. Given military associations, the Hampshire County now has the second largest Nepali population, with the Nepali now making up close to 10% of the population. Nepal sits between China and India, two countries with higher prevalence rates of HBV and HCV, but relatively little is known about prevalence in the Nepali community, with no published studies in the UK. Methods: To help design a culturally sensitive testing strategy for HBV and HCV (as advocated by NICE) we conducted focus groups sessions in the Nepali community. Nepali moderators guided sessions to study the beliefs, understanding and perceptions towards liver disease. Results: 32 Nepali members attended the focus group sessions, with groups divided by sex and age (< 30yrs, or > 30 yrs). A thematic analysis approach was used to analyse results. Perceptions of Liver disease: "It is not a communicable disease" "In Nepal water is the main cause of hepatitis" "Mainly alcoholic and smokers get this disease" "I do not think people hate the person….it would not be considered as bad as leprosy disease" Treatment options: "In Nepal herbal medicine is better for jaundice….necessary to drink lot of water and fruits" Knowledge and outreach: "We need to know the function of liver. Then we understand the issue." "Newspaper for the people who can read but for us who cannot read, radio and TV is better" "What the doctor said, we trust on it" Conclusion: NICE guidelines advocate testing at-risk migrant groups for HBV and HCV at an early (asymptomatic) stage. Here, all groups identified liver disease with jaundice or symptoms. Different viewpoints were expressed based on age; younger Nepali members associating a greater stigma to liver disease and hepatitis. All groups expressed a sincere wish to gain greater knowledge about liver disease and to interact with primary care. The study also identified the functional illteracy of many Nepali, and the potential need to modify approaches away from written media. Reference: 1 NICE (National Institute for Health and Care Excellence), Hepatitis B and C, ways to promote and offer testing to people at increased risk of infection, 2012 Disclosure of Interest: None Declared.